Constellations of Memory: The Historicity of Hungarian Yizker-Bikher - Lujza Vallo (Slovo, 2021)
The following paper reviews Central European memorial volumes created within the borders of modern day Hungary from the 1960s onwards. Using six sporadically chosen primary sources as the subjects of analysis, the argument of this piece will centre around finding out whether memorial volumes or in Yiddish yizker-bikher are reliable testimonial documents based on their historical veracity. The paper argues that the historicity of Eastern European memorial books can range from personal tales of community living, to more accurate historical monographs, aiming to fill out gaps in trans-generational remembrance. The analysis is then divided into four chapters each introducing a relevant perspective when evaluating yizker-bikher: Firstly, it will examine the six memorial books as linguistic sources by showcasing their characteristic narrative techniques. Secondly, the paper will contrast the historical contents covered in the texts with the findings of modern Hungarian Holocaust research. Thirdly, previous academic perspectives categorising yizker-volumes are introduced, leading the paper to a brief conclusion. A final evaluation is conducted to highlight the examined volumes as the sources of microhistory that carry anthropological research potential rather than the ability to provide overarching solutions to the gaps in archival Holocaust history.
Keywords: Holocaust history; Memorial volumes; Hungary; Yizker-bikher